Mom and Dad, We Need to Talk - Huddleston, Cameron (Ascent Audio, 2019)
As your parents age, you may find that you want or need to broach the often-difficult subject of finances. In Mom and Dad, We Need to Talk: How to Have Essential Conversations with Your Parents About Their Finances, you'll learn the best ways to approach this issue, along with a wealth of financial and legal information that will help you help your parents into and through their golden years. Sometimes parents are reluctant to address money matters with their adult children, and topics such as long-term care, retirement savings (or lack thereof), and end-of-life planning can be particularly touchy. In this book, you'll hear from others in your position who have successfully had "the talk" with their parents, and you'll learn about a variety of conversation strategies that can make talking finances more comfortable and more productive. - Learn conversation starters and strategies to open the lines of communication about your parents' finances - Discover the essential financial and legal information you should gather from your parents to be prepared for the future - Gain insight from others' stories of successfully talking money with aging parents - And more.